North Central Asia isotopic database for archaeological samples - Smithers, R; Miller, A R Ventresca; Fernandes, R (Data in brief, 2024)
The North Central Asia Isotopic Database (NCAID) is an open-access dataset of stable isotope measurements from archaeological remains, spanning from the Early Neolithic until present-day in North Central Asia. With 3,143 individual entries corresponding to data accumulated over more than 20 years of research, this comprehensive dataset encompasses measurements of stable carbon and nitrogen isotopes in organic fractions from archaeological humans, animals, and plants. NCAID incorporates diverse supporting information, providing geographical information, archaeological context descriptions, and chronology. This resource facilitates research into past human lifeways, paleo-environments/climates, and animal management practices throughout North Central Asia and will be continually updated as more novel data is released.
Keywords: Bioarchaeology; Isotopes; Archaeology; Collagen; Central Asia